The Influence of the Application of the Discussion Learning Method on Students' Learning Interest at SMK Negeri 1 Pangkep - Nasra Maulidya; Haedar Akib; Sitti Hardiyanti Arhas (ASHA Publishing, 2024)
Learning interests play a very important role in learning activities. When students have a high interest in the subject or topic being studied, students feel dominantly focused, engaged, and have a desire to learn well in learning activities. This research was carried out to evaluate the influence of the application of discussion learning methods on students' learning interests. To achieve this goal, data collection techniques are used through questionnaires, documentation, and interviews. The number of people taken as a sample in this study was 80 people using a simple random sampling technique. From the data collected, the results of the study were processed using descriptive analysis techniques and inferential analysis techniques to determine the influence of the application of discussion learning methods on students' learning interests. The results of the study showed that: (1) Grade XI students of Office Management and Business Services in carrying out discussion methods to increase students' interest in learning include the concentration of attention in learning, the presence of a feeling of pleasure, and the willingness to learn. (2) The correlation coefficient (r) was obtained which was 0.748% which means that the relationship between the discussion method and students' learning interests was 74.8%. Meanwhile, the determinant coefficient (r-square) was obtained 0.560 which means that the influence of discussion on students' learning ability was 56.0% while 44% of students' learning interest was influenced by other factors that were not explained in this study.